Optimizing Emergency Diagnostic Imaging in Patients with Pulmonary Embolism in the Emergency Room - Petko Stefanovski; Vladimir Radev; Nela Stefanovska; Nachko Tocev; Slavejko Bogdanov; Hristo Gigov (Journal of Biomedical & Clinical Research)
We performed a retrospective evaluation of the criteria for suspected pulmonary embolism (PE) and requests for computed tomography angiography (CTA) by the emergency room (ER) teams. Simultaneously, we tried to find irregularities in their work. Then we designed new behavioral protocols, and yearly we evaluated the effect on the workload of the computed tomography (CT) unit of the Roentgenology and Radiology at the University Hospital – Pleven and the total impact on the behavior of the teams in cases of suspected for PE. The data from before and after the intervention was evaluated. After the implementation of the protocols, matching the criteria of PE rule-out criteria (PERC), the number of D-dimer testing, echocardiography, and computed tomography pulmonary angiographies (CTPA) was significantly higher. We found that the number of patients urgently transported for primary thrombectomy had increased, and the reduction of PE mortality in the Emergency Unit proves the safety of our intervention. Overall, the intervention in the attitude of the ER teams has a significant positive effect on the management of patients with suspected PE.